Optical Forces on an Oscillating Dipole Near VO2 Phase Transition - Szilard, Daniela; Abrantes, Patrícia P.; Pinheiro, Felipe A.; Rosa, Felipe S. S.; Farina, Carlos; Kort-Kamp, Wilton J. M. (Universe (Basel), 2021)
We investigate optical forces on oscillating dipoles close to a phase change vanadium dioxide (VO2) film, which exhibits a metal-insulator transition around 340 K and low thermal hysteresis. This configuration emulates the interaction between an illuminated nanosphere and an interface and we employ a classical description to capture its important aspects. We consider both electric and magnetic dipoles for two different configurations, namely with the dipole moments parallel and perpendicular to the VO2 film. By using Bruggeman theory to describe the effective optical response of the material, we show that the thermal hysteresis present in the VO2 transition clearly shows up in the behavior of optical forces. In the near-field regime, the force on both dipoles can change from attractive to repulsive just by heating (or cooling) the film for a selected frequency range. We also verified that the optical forces are comparable to the Casimir-Polder force in a similar system, revealing the possibility of modulating or even changing the sign of the resultant force on an illuminated nano-object due to the presence of a thermochromic material. We hope that this work contributes to set the grounds for alternative approaches to control light-matter interactions using phase-change materials.